Estudo dos efeitos da criação de morfologias antropogênicas em área de mineração - Paschoal, Letícia Giuliana [UNESP] (2014)
Open air mining activities are directly associated to changes in natural landscapes. This work had as main objective identify and analyze the changes imposed by the geomorphological dynamics of anthropic actions linked to mining activity of various types, emphasizing the changes of relief and sedimentation in valley bottom areas, and their implications on physical environmental systems. We opted for the choice of sub-basins inserted in the Corumbataí river basin as the unit of study, in that they are highly impacted by exploitation of the main non-metallic minerals used by the segment of industry and construction, namely: Ribeirão Santa Gertrudes, Córrego das Taipas, Córregos Marroti and Gonçalves and, Ribeirão das Araras basin, where mineral exploitation of clay, sand, limestone and basalt occur respectively. The research was developed in accordance with the systems perspective with emphasis on anthropogenic geomorphology. Maps of land use, combined with the evolutionary geomorphological mapping, both dated 1962, 1988 and 2006 or 2010, at 1:10,000 scale, were made and helped with the choice of collection site sediment dated by the 210Pb method in these sub-watersheds. Analysis of the results was performed by comparing data obtained in different scenarios of land use maps and geomorphological evolution, as well as the assessment of anthropogenic interference in the sediment loads of the valley bottom, which allowed evaluating the dynamics of the processes historical accumulation of river sediments in some of the sub-basins, between the years 1999 and 2012. The changes in the land use of these sub-basins, imply changes in the dimensions of the relief that can be measured, such as topographic ruptures, furrows, increasing the area of fluvial accumulation, emergence of artificial lakes, fund types of valleys, cuts, landfills, mining levels in quarries, accumulation area of lowland and terrace river under anthropogenic interference...